Oooo ok
I don’t now true this or no
But answer is 13
The correct answer is y=1/2x+1
Answer: The correct option is A.
Step-by-step explanation: We are given a polynomial which is a sum of other 2 polynomials.
We are given the resultant polynomial which is : ![8d^5-3c^3d^2+5c^2d^3-4cd^4+9](https://tex.z-dn.net/?f=8d%5E5-3c%5E3d%5E2%2B5c%5E2d%5E3-4cd%5E4%2B9)
One of the polynomial which are added up is : ![2d^5-c^3d^2+8cd^4+1](https://tex.z-dn.net/?f=2d%5E5-c%5E3d%5E2%2B8cd%5E4%2B1)
Let the other polynomial be 'x'
According to the question:
![8d^5-3c^3d^2+5c^2d^3-4cd^4+9=x+(2d^5-c^3d^2+8cd^4+1)](https://tex.z-dn.net/?f=8d%5E5-3c%5E3d%5E2%2B5c%5E2d%5E3-4cd%5E4%2B9%3Dx%2B%282d%5E5-c%5E3d%5E2%2B8cd%5E4%2B1%29)
![x=8d^5-3c^3d^2+5c^2d^3-4cd^4+9-(2d^5-c^3d^2+8cd^4+1)](https://tex.z-dn.net/?f=x%3D8d%5E5-3c%5E3d%5E2%2B5c%5E2d%5E3-4cd%5E4%2B9-%282d%5E5-c%5E3d%5E2%2B8cd%5E4%2B1%29)
Solving the like terms in above equation we get:
![x=(8d^5-2d^5)+(-3c^3d^2+c^3d^2)+(5c^2d^3)+(-4cd^4-8cd^4)+(9-1)](https://tex.z-dn.net/?f=x%3D%288d%5E5-2d%5E5%29%2B%28-3c%5E3d%5E2%2Bc%5E3d%5E2%29%2B%285c%5E2d%5E3%29%2B%28-4cd%5E4-8cd%5E4%29%2B%289-1%29)
![x=6d^5-2c^3d^2+5c^2d^3-12cd^4+8](https://tex.z-dn.net/?f=x%3D6d%5E5-2c%5E3d%5E2%2B5c%5E2d%5E3-12cd%5E4%2B8)
Hence, the correct option is A.
Answer:
1.4
Step-by-step explanation: